Persepsi Orangtua Tentang Pendidikan Tinggi Bagi Anak Perempuan Di Desa Simatorkis Kec. Dolok Kab. Padanglawas Utara - Sawaluddin Siregar (Jurnal Kajian Gender dan Anak, 2020)
This study is an attempt to find out the perceptions of parents about higher education for girls in the village of Simatorkis, Kec. Dolok Kab. Padanglawas North. The question the author wants to pursue is the perception of parents in providing higher education opportunities to their daughters. After systematic research, it can be seen that parents' perceptions of higher education for their daughters are as follows: Higher education is important for girls to be able to compete with an increasingly modern era, to be successful people, knowledgeable and well-known in society that will become proud. Factors that hinder higher education for girls in Simatorkis village are social culture, economic conditions, psychological factors. Reasons and considerations of parents providing opportunities for higher education for their children is the desire to change their destiny, and awareness of parents who think that higher education is important for boys and girls without having to make a difference